La carga de la prueba en el proyecto de reforma del Código Procesal Civil peruano - Asencio Mellado, José María (2025)
In this article, the author addresses the regulation of the burden of proof in the Draft Reform of the Peruvian Civil Procedure Code, providing a critical analysis of the draft’s legal provisions while formulating suggestions, adjustments, and proposals.